The Relationship Between Self-Regulation, Self-Efficacy, and Psychological Well-Being Among the Salahaddin University Undergraduate Students in Kurdistan - Salleh, Reben Ramadhan; Ismail, Nik Ahmad Hisham; Idrus, Faizah (International Journal of Islamic Educational Psychology, 2021)
The relationship between self-regulation, self-efficacy, and psychological well-being has become a hot topic in recent years. This research objective examines the prevalence level, self-regulation, self-efficacy, and psychological well-being among Salahaddin University undergraduate students in Kurdistan. Quota sampling was used in the study, and 407 respondents were chosen for it. Descriptively, Pearson correlation and multiple regression analysis approaches were applied. The research showed a low level of self-regulation and self-efficacy among the sample students. However, psychological well-being was found to be high. The study also found that self-regulation, self-efficacy, and psychological well-being are positively correlated and statistically significant. This study concluded that self-regulation was the only factor influencing psychological well-being. Therefore, this research recommends emphasizing students' self-regulation to enhance their well-being.